Pengaruh Metode Make And Match terhadap Kemampuan Kognitif Anak Usia 5-6 Tahun - Siregar, Fatimah Nayla Zaskia; Masganti Sit (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to determine the influence of the make and match method on the cognitive ability of children aged 5-6 years in RA Ibnu Halim Tanjung Mulia Hilir. This research uses a quantitative approach method by carrying out Field Research. This study presents data in the form of numbers using statistical data analysis which has the purpose of testing hypotheses and data analysis using the Paired Sample t Test. The results of the research showed that the average cognitive development of children before and after treatment was 7.70 to 13.30. The hypothesis testing also supports this finding, with a significance value of 0.00 (< 0.05), indicating a statistically significant difference. In this study, a worksheet presttest and a posttest of the geometric shape game box media were used. The conclusion of this study is that improving the cognitive ability of children aged 5-6 years is more influential if they use media rather than using worksheets. Based on the analysis that has been carried out in this study, the geometric shape of the game box media affects the cognition of 5-6 year old children in using the make and match method.